The portrayal of sexual abuse in Zakes Mda's The Madonna of Excelsior and J.M. Coetzee's disgrace: : a comparative study - Makgato, Kgokologa Saltiel (My University, 2010)
This dissertation examines the way in which two South African novelists, Zakes Mda and J.M. Coetzee, portray the sexual abuse of women during the apartheid and post-apartheid eras. The two selected novels used in this research are The Madonna of Excelsior (2002) by Mda and Disgrace (2000) by Coetzee. The research, furthermore, analyses the attitudes of the sexual abusers and their victims in both eras as well as examines the effects of socio-economic imbalances that might have prompted the men to sexually abuse women whom they should be offering protection against any form of violence and abuse. The study furthermore identifies and analyses the factors that hinder victims from reporting their sexual abuse to the police. Finally, this dissertation also presents a comparative study of the differences and the similarities between the way the two novelists portray sexual abuse.
Thesis (M.A. (English) -- University of Limpopo, 2010
Keywords: Portrayal of women abuse; Zakes Mda essays; Sex crimes; Novelists, English -- South Africa